Perbedaan Nilai Vo2 Maks Saat Menstruasi Dan Tidak Menstruasi Pada Atlet Pencak Silat Kota Semarang Tahun 2020 - Safira Safira; Anies Setiowati; Nanang Indardi; Gustiana Mega Anggita; Siti Baitul (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
Female members of the martial arts in Semarang City. Sampling using purposive sampling technique. The instrument used is the Bleep Test. Data analysis used statistical test T-test which was processed with SPSS 16.0 for windows. The results showed a difference of two means it is known that the average VO₂ MAX result during menstruation is 4.89 ml/kg.bb/minute and the average VO₂ MAX result when not menstruating is 5.29 ml/kg.bb/minute. Research conclusions There is a significant difference in the value of VO₂ Max during menstruation and not menstruation in Pencak Silat athletes in Semarang City in 2020. Suggestions for healthy living patterns and habits with balanced nutrition and increasing endurance by exercising regularly and routinely.